Effects of Combustible Cigarettes and Heated Tobacco Products on Systemic Inflammatory Response in Patients with Chronic Inflammatory Diseases - Kastratovic, Nikolina; Zdravkovic, Natasa; Cekerevac, Ivan; Sekerus, Vanesa; Harrell, Carl Randall; Mladenovic, Violeta; Djukic, Aleksandar; Volarevic, Ana; Brankovic, Marija; Gmizic, Tijana; Zdravkovic, Marija; Bjekic-Macut, Jelica; et al. (Diseases, 2024)
Smoke derived from combustible cigarettes (CCs) contains numerous harmful chemicals that can impair the viability, proliferation, and activation of immune cells, affecting the progression of chronic inflammatory diseases. In order to avoid the detrimental effects of cigarette smoking, many CC users have replaced CCs with heated tobacco products (HTPs). Due to different methods of tobacco processing, CC-sourced smoke and HTP-derived aerosols contain different chemical constituents. With the exception of nicotine, HTP-sourced aerosols contain significantly lower amounts of harmful constituents than CC-derived smoke. Since HTP-dependent effects on immune-cell-driven inflammation are still unknown, herein we used flow cytometry analysis, intracellular staining, and an enzyme-linked immunosorbent assay to determine the impact of CCs and HTPs on systemic inflammatory response in patients suffering from ulcerative colitis (UC), diabetes mellitus (DM), and chronic obstructive pulmonary disease (COPD). Both CCs and HTPs significantly modulated cytokine production in circulating immune cells, affecting the systemic inflammatory response in COPD, DM, and UC patients. Compared to CCs, HTPs had weaker capacity to induce the synthesis of inflammatory cytokines (IFN-γ, IL-1β, IL-5, IL-6, IL-12, IL-23, IL-17, TNF-α), but more efficiently induced the production of immunosuppressive IL-10 and IL-35. Additionally, HTPs significantly enhanced the synthesis of pro-fibrotic TGF-β. The continuous use of CCs and HTPs aggravated immune-cell-driven systemic inflammation in COPD and DM patients, but not in UC patients, suggesting that the immunomodulatory effects of CC-derived smoke and HTP-sourced aerosols are disease-specific, and need to be determined for specific immune-cell-driven inflammatory diseases.